Breastfeeding Practices Among Women in a Selected Rural Area (Journal of Preventive and Social Medicine, 2021)
Background: Breast milk is the only source of nutrition freely available to the newborn from the mother. Breast feeding is the fundamental right of every child. It is the safest, least allergic and best infant feeding method. Absence of breastfeeding significantly increases the risk for a large number of acute and chronic diseases. WHO recommends the practice of exclusive breastfeeding as an essential component of infant nourishment. This present study was conducted to find out the breastfeeding practice among the women of rural areas of Bangladesh.Methods: This cross-sectional type of descriptive study was carried out from October, 2015 to April, 2016 in Kaliakair Upazila under the district of Gajipur. Seven hundred and eighty mothers having children between 6-24 months’ age group were interviewed. Data were collected by face-to-face interview with the respondents through a pretested semi structured questionnaire. The study place was selected conveniently and the sampling technique was purposive type of non-probability sampling.Results: The mean age of the respondents was 24 (±4.493) years and the mean age of the children was 16.84 (±5.766) months. The majority (44%) of the respondents belonged to the education level of class VI-X. Most (93.6%) of the respondents were housewives. Around two-third (63.9%) of the mothers were from nuclear families while one-third (36.1%) were from joint families. Majority (55.4%) of the respondents were from middle income group (10,001- 30,000 Tk. monthly income). Among all, 91% had knowledge about the importance of breastfeeding. Most (98.8%) of the mothers breastfed their babies. Among the breastfed mothers, 55.6% practiced exclusive breastfeeding. And colostrum was given by 95.5% mothers. Lack of knowledge and superstition was the main causes not proving colostrum. Breastfeeding was started right after birth by 73.7% mothers while 24.3% started within 5 days. More than half of the mothers continued to breastfeed beyond 16 months. Among the mother without exclusive breastfeeding, 44.4% gave various types of additional food to their babies including powder milk (57%), cow's milk, shuji, water and some other food, the main reason for giving additional food was insufficiency of breast milk (82.2%). Most (90.6%) of the mothers started complimentary feeding between 6-10 months of age.Conclusion: In depth community based epidemiological studies may be carried out by covering the whole population to explore the situation in detail.JOPSOM 2020; 39(2): 50-58